Perlindungan Hukum Anak Korban Eksploitasi Sebagai Publik Figur di Media Sosial - Garry, Garry; Harefa, Beniharmoni (Universitas Semarang, 2024)
This research examines the protection of children as public figures on social media. Involving children in the world of work, or what is known as child labor, has several applicable provisions because employing children is only allowed to develop a child's interests and talents. Exploitation can occur if children are forced to work as public figures on social media. Law Number 17 of 2016 concerning child protection was created in order to provide protection for children from all actions that are detrimental to the child's growth and development. In addition, the role of the government through institutions related to child protection is one of the keys to reducing the number of cases of child exploitation. The research method used is normative juridical type with a statutory approach and a comparative approach supported by primary, secondary, and tertiary legal materials. The results of this research show that there are regulations governing the prevention of child exploitation and provisions for child labor, along with the role of KPAI as a child protection institution, so that these two components should be able to suppress cases of child exploitation of public figures on social media.Penelitian ini mengkaji mengenai perlindungan anak sebagai publik figur dalam media sosial. Melibatkan anak dalam dunia kerja atau disebut dengan pekerja anak memiliki beberapa ketentuan yang berlaku karena dalam mempekerjakan anak hanya boleh dalam rangka mengembangkan minat dan bakat seorang anak. Eksploitasi dapat terjadi jika anak dipaksa untuk menjadi pekerja sebagai publik figur di media sosial. Undang-Undang Nomor 17 tahun 2016 tentang perlindungan anak telah dibuat dalam rangka memberikan perlindungan bagi anak dari segala tindakan yang merugikan tumbuh kembang anak. Di samping itu peran dari pemerintah melalui lembaga terkait perlindungan anak merupakan salah satu kunci dari penekanan angka eksploitasi anak. Metode penelitian yang digunakan adalah jenis yuridis normatif dengan pendekatan perundang-undangan, pendekatan komparatif yang didukung bahan-bahan hukum primer, sekunder, tersier. Hasil dari penelitian ini menunjukan bahwa sudah ada regulasi yang mengatur mengenai pencegahan eksploitasi anak dan ketentuan bagi pekerja anak beserta peran KPAI sebagai lembaga perlindungan anak sehingga dengan dua komponen tersebut seharusnya mampu menekan kasus eksploitasi anak publik figur di media sosial.